Ubiquitous Project-Based Learning Instructional Design in Islamic College - Mochamad Desta Pradana; Punaji Setyosari; Saida Ulfa; Made Duananda Kartika Degeng (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2024)
The right learning strategy provides benefits in mastery of learning, allowing students to collaborate and interact in implementing and creating learning projects. Through Ubiquitous Project Based Learning (UPjBL), Instructional Design fully contributes to achieving optimal learning objectives for students. This study aims to develop UPjBL Learning Design and determine the feasibility of the results. The development method for education uses the ADDIE development model stages. The data collection technique uses an instrument in the form of a validation assessment sheet and a closed question instrument in the form of a five-point Likert scale. The development procedure is done by analysis, design, development, implementation and evaluation. The study found that the Ubiquitous Project Based Learning (UPjBL) learning design is valid and feasible. It is known that the product developed has a feasibility value of 4.5 which means that the product is included in the extraordinary category or is very possible to use in the learning process. The combination of Ubiquitous learning and Project-based learning has a UPjBL learning model based on the Constructivist approach. This approach emphasizes that the learning process is centred on students by constructing knowledge obtained contextually. The lecture program units and teaching materials for Information and Communication Technology with primary computer material are adjusted to the curriculum and characteristics of students.